PENGARUH RISIKO PERUSAHAAN, CAPITAL INTENSITY, PROFITABILITAS, DAN PERTUMBUHAN PENJUALAN TERHADAP PENGHINDARAN PAJAK - Putri Nadiah Zain Samporna; Indrayati; Ahmad Jarnuzi; Fathimatus Zahro Fazda Oktavia (Jurnal Akuntansi Bisnis dan Humaniora, 2022)
The purpose of this research was to test the effect of corporate risk, capital intensity, profitability, and sales growth on tax avoidance. The research object was manufacturing companies in the consumer goods sectors listed on the Indonesia Stock Exchange during the 2016-2020 period. The number of samples determined in this research was 26 companies by using purposive random sampling. This research was associative quantitative research, this research used the 26th version of SPSS as the data analysis tool. The results showed that capital intensity and profitability had a negative and significant effect on tax avoidance, while company risk and sales growth did not affect tax avoidance. Simultaneously corporate risk, capital intensity, profitability, and sales growth had a significant affect on tax avoidance. The results of this research are expected to help the government and companies to control tax avoidance practices.